Effect of soy protein a humidifier in the qualitative characteristics of the Barker factory of beef and chicken meat elderly (Baghdad Science Journal, 2006)
The purpose of this study was to know the effect of adding different percentages of soy protein a humidifier to mix Sarcoma Barker component of the beef mixture Alkhalt added Alber elderly chicken with five ratios were manufacturing Alberkr discs for sensory evaluation